2016
DOI: 10.1002/14651858.cd011718.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Heparin for the prevention of intraventricular haemorrhage in preterm infants

Abstract: There is very limited data on the effect of prophylactic administration of heparin on the incidence and severity of IVH in very preterm neonates. Both the identified trials used heparin in the context of maintaining umbilical line patency and not specifically as an agent to prevent germinal matrix-intraventricular haemorrhage. Given the imprecision of our estimates, the results of this systematic review are consistent with either a benefit or a detrimental effect of heparin and do not provide a definitive answ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Interestingly, low‐dose heparin has been proposed as a possible prophylactic treatment for IVH, the rationale being that thrombi formation the central venous system may contribute to the development of IVH 66 . While a meta‐analysis showed no benefit of low‐dose heparin (1 U/mL), it also showed no harm at that dose 67 . Therefore, decreasing the anticoagulation requirement to the low‐dose heparin range may be compatible with artificial placenta use in EPT neonates.…”
Section: Designing Next‐generation Oxygenators For the Artificial Plamentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, low‐dose heparin has been proposed as a possible prophylactic treatment for IVH, the rationale being that thrombi formation the central venous system may contribute to the development of IVH 66 . While a meta‐analysis showed no benefit of low‐dose heparin (1 U/mL), it also showed no harm at that dose 67 . Therefore, decreasing the anticoagulation requirement to the low‐dose heparin range may be compatible with artificial placenta use in EPT neonates.…”
Section: Designing Next‐generation Oxygenators For the Artificial Plamentioning
confidence: 98%
“…66 While a meta-analysis showed no benefit of low-dose heparin (1 U/mL), it also showed no harm at that dose. 67 Therefore, decreasing the anticoagulation requirement to the low-dose heparin range may be compatible with artificial placenta use in EPT neonates. There are several avenues by which the need for anticoagulation in an oxygenator can be reduced.…”
Section: Minimal Anticoagulationmentioning
confidence: 99%
“…e human CCVD-related diseases associated with genes were secured from the curative targets database such as the Online Mendelian Inheritance in Man (OMIM, http:// www.omim.org/) and Pharmacogenomics Knowledgebase (PharmGKB; http://www.pharmgkb.org) [29][30][31][32]. e keywords were "stroke," "anti-platelet aggregation," "atherosclerosis," "improving microcirculation," and "antithrombin" [33][34][35].…”
Section: Target Fishing Drug Target Indentifying Is Momentousmentioning
confidence: 99%
“…A recent review found that antithrombin administration doesn't reduce the incidence of IVH in very low-birth-weight preterm when compared to placebo, no treatment, and heparin [59]. Additional studies are warranted to illustrate the effect of heparin as a preventive agent for IVH [60].…”
Section: Intraventricular Hemorrhage (Ivh)mentioning
confidence: 99%
“…A recent review found that antithrombin administration doesn't reduce the incidence of IVH in very low-birth-weight preterm when compared to placebo, no treatment, and heparin [59]. Additional studies are warranted to illustrate the effect of heparin as a preventive agent for IVH [60].Lung Injury: Surfactant deficiency, immature lung structure, and poorly developed respiratory mechanisms are the main causes of lung injury among preterm neonates. Therefore, respiratory support is generally recommended for that high-risk group to maintain functional residual capacity and avoid lung damage.…”
mentioning
confidence: 99%